Endophytic Beauveria bassiana (Ascomycota: Hypocreales) alters Helicoverpa gelotopoeon`s (D.) (Lepidoptera: Noctuidae) life cycle and reproductive parameters - Florencia Vianna; Sebastian Pelizza; Leticia Russo; Natalia Allegrucci; Ana Scorsetti (Journal of Plant Protection Research, 2018)
Bollworms comprise the most harmful and economically relevant species of lepidopteran. Helicoverpa gelotopoeon (D.) (Lepidoptera: Noctuidae) is native to America and affects many crops. Tobacco is an industrial crop in which methods of pest control rely mainly on the application of insecticides. To develop new eco-friendly strategies against insect pests it is very important to overcome the side effects of insecticides. The utilization of fungal entomopathogens as endophytes is a new perspective that may accomplish good results. The present study aimed to evaluate the ability of endophytic Beauveria bassiana (Bals.-Criv.) Vuill. to affect H. gelotopoeon life parameters and feeding behavior on tobacco plants. Beauveria bassiana LPSC 1215 as an endophyte did not reduce the amount of vegetal material consumed by H. gelotopoeon larvae but affected the life cycle period of the plague, particularly the larval and adult stages. Also, egg fertility was affected since adults laid eggs that were not able to hatch. The results of this investigation provide new information on endophytic entomopathogen potential to be incorporated in Integrated Pest Management (IPM) programs.